Stoic Consolations - Sherman, Nancy (Conatus - Journal of Philosophy, 2023)
In this paper I explore the Stoic view on attachment to external goods, or what the Stoics call “indifferents.” Attachment is problematic, on the Stoic view, because it exposes us to loss and exacerbates the fragility that comes with needing others and things. The Stoics argue that we can build resilience through a robust reeducation of ordinary emotions and routine practice in psychological risk management techniques. Through a focus on selected writings of Seneca as well as Cicero’s Tusculan Disputations and Marcus Aurelius’s Meditations, I nonetheless ask whether Stoicism leaves any room for grief and distress. I argue that it does, and that consolation comes not from a retreat to some inner citadel, but from the support and sustenance of social connections.